'Quality of life' concept in Cohesion Policy evaluation in Poland, 2004–2020. (October 2022) - Kupiec, Tomasz; Wojtowicz, Dominika
Abstract: Quality of life (QoL) is a fashionable concept widely used not only in many scientific fields but also in strategic documents, political speeches, and newspaper headlines. Although QoL is a crucial element of political agendas and a goal of public policies, there is little evidence on how this concept has been incorporated in policy analysis and evaluation. This study presents how the QoL has so far been defined, contextualised, and measured in the European Union Cohesion Policy evaluation in Poland, based on the analysis of 1431 evaluation reports for the period 2004–2020. The findings show that the interest in the QoL is growing, and almost one-third of reports refer to the term. However, the concept is usually not clearly defined, and the number of evaluations with actual questions concerning QoL is limited. Moreover, the methodological approach to QoL measurement is rudimentary, limited to surveys of beneficiaries or end-users. Highlights: Quality of life is not for the moment a fully-fledged criterion in policy evaluation. Typical understanding of the quality of life in evaluation is narrow and intervention-centric. Urgent debate is needed on the acceptable quality of life measurement approaches within EU policies' evaluation.